Spontaneous Non Ischaemic Blue Finger: A Rare and Benign Phenomenon - Franco, Daniela (2015)
The spontaneous non-ischaemic blue finger is a rare and benign disorder, characterized by purple discoloration of a finger, with complete resolution. This article reports the case of a woman of 88 years, which after a few hours of stay in the emergency department developed without associated trauma, a purplish color of the 3rd finger of the right hand, with a palpable pulse and without temperature changes or pain. The etiological investigation was negative. The patient was assessed one week after the event and showed completeresolution. There are several diseases that share the same signs and symptoms, as such the diagnosis is based on the spontaneous violaceous color sparing the finger tip, and fast resolution without treatment. Though being a harmless phenomenon, it requires early assessment for timely differential diagnosis with severe pathologies.